Inclusive Methods in Architectural and Strategic Planning (EAAE Annual Conference Proceedings, 2023)
In the last ten years the Faculty of Architecture at the University of Zagreb has been developing and practicing inclusive methodologies for innovative planning and programming developments in the public domain. Stakeholders from different sectors (civil, government, academic and business) have various perspectives on what public interest is and how it should be achieved. In complex strategic decision making SDGs play an important role as criteria in evaluating certain action, solution or policy and its benefits to the environment, the social realm or economics.